A coupled model for sediment transport dynamics and prediction of seabed morphology with application to 1DH/2DH coastal engineering problems - Vasileios Afentoulis; Andreas Papadimitriou; Kostas Belibassakis; Vasiliki Tsoukala (Oceanologia)
Coastline retreat poses a threat to nearshore environment and the assessment of erosion phenomena is required to plan the coastal engineering works. The hydro-morphodynamic response of a beach to natural and artificial forcing factors differ considerably, as the nearshore processes are especially complex and depended on a multitude of parameters, including prevailing wave and hydrodynamic conditions, beach topography, sediment characteristics and the presence of coastal protection works. The present study serves the purpose of numerically evaluating nearshore morphological processes and ultimately assessing the capacity of coastal defence structures to control beach erosion. For this reason, a new sediment transport model including unsteady effects and swash zone morphodynamics, was coupled to the highly nonlinear Boussinesq wave model FUNWAVE-TVD, providing integrated predictions of bed level evolution, across various timescales of interest. The compound model was validated thoroughly against laboratory data and other numerical investigations. Overall, a good agreement between experimental and numerical results was achieved for a number of test cases, investigating the effects of different types of shore protection structures. The proposed integrated model can be a valuable tool for engineers and scientists desiring to obtain accurate bed level predictions, over complex mildly and steeply sloping sea bottoms composed of non-cohesive sediment particles.